Assessing the causes of schedule and cost overruns in South African mega energy projects: a case of the Limpopo Province - Tshidavhu, Fhumulani Judith (My University, 2020)
Cost and schedule overruns are the most common challenges in mega construction projects around the globe. The frequency of megaprojects failing to be completed on time and within budget is creating a poor reputation in the construction industry. This research aimed to assess the causes of cost and schedule overruns in the construction of megaprojects in South Africa. The objectives were to identify the local challenges militating against a project’s implementation success, to analyse the local conditions that could contribute to project implementation sluggishness, to assess planning and implementation practices in such projects and to assess the local expertise and acumen during the front-end project preparation process. Quantitative research method was employed. Questionnaires were used to collect data from engineers, quantity surveyors, architects, contractors and project managers. Limitation of the study is that leadership instability at Eskom, the South African public electricity utility company, has occasioned a climate of mistrust to outsiders making assessing informative sources difficult. Data were analysed using mean item score. The analysis indicates that poor site management, inadequate managerial skills, poor monitoring and control, lack of experience, poor financial planning, changes in the scope of work on site, variation orders, omission and errors in the Bill of Quantities, and unstable management structure were the major causes of cost and schedule overruns. Specific solutions that mitigate the causes of schedule and cost overrun should be investigated in future studies
Assessing the cause of schedule and cost overrun in South African Mega projects: a case of Limpopo Province in South Africa
A research report submitted to the School of Construction Economics and Management, Faculty of Engineering and Built Environment, University of Witwatersrand in fulfilment of the requirements for the degree of Master of Science, 2019
Keywords: Project management; Risk management